Designing Games for Moral Learning and Knowledge Building. Issue 4 (June 2019) - Schrier, Karen
How can we better learn about and teach moral thinking and skills? How can we solve moral problems? One possible way is to create and use moral learning games, or games that enable players to work on moral scenarios, make moral choices, and gain relevant skills. One possible subcategory of these games is moral knowledge games, or games that aim to solve real-world moral problems and create new knowledge about morality. This article systematically analyzes relevant literature and related games and media to uncover a preliminary set of design principles for creating moral learning games and moral knowledge games. Frameworks such as the Elemental Tetrad, Mechanics, Dynamics, and Aesthetics (MDA), and Ethics Practice and Implementation Categorization Framework (EPIC) were used to analyze individual games and media. Ten different categories of principles emerged, along with 95 possible subprinciples. Implications, next steps, and limitations of this analysis were also discussed.